PENERAPAN LAYANAN BIMBINGAN KELOMPOK TEKNIK GAME BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENGELOLA EMOSI SISWA KELAS VIII SMP NEGERI 36 PALEMBANG - Irdha Amanda; Eibi Pramitha Miranda, Rani Mega Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to improve students' ability to manage emotions through group guidance services using techniques game based learning by using media board game my emotions. Emotional intelligence is an important factor in students' academic success and social adaptation, but in reality there are still many students who have difficulty recognizing and managing their emotions appropriately. The research method used was Guidance and Counseling Action Research (PTBK) which involved 8 class VIII students at SMP Negeri 36 Palembang in two cycles. Data collection techniques use observation instruments and questionnaires. The research results showed a significant increase in students' ability to manage emotions. The average score increased from the "low" category at pre-cycle to "medium" after cycle I, and reached "high" in cycle II. This research reinforces the importance of implementing group guidance services using techniques game based learning in improving students' ability to manage emotions effectively.